2006
DOI: 10.2527/2006.841145x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of feedlot feed efficiency, performance, and feeding behavior with metabolic rate, methane production, and energy partitioning in beef cattle1

Abstract: Residual feed intake (RFI) is the difference between the actual and expected feed intake of an animal based on its BW and growth rate over a specified period. The biological mechanisms underlying the variation in feed efficiency in animals with similar BW and growth rate are not well understood. This study determined the relationship of feedlot feed efficiency, performance, and feeding behavior with digestion and energy partitioning of 27 steers. The steers were selected from a total of 306 animals based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

53
375
9
35

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 476 publications
(481 citation statements)
references
References 22 publications
53
375
9
35
Order By: Relevance
“…This is in agreement with studies in cattle where RFI was correlated with improved dry matter digestibility (Richardson et al, 2004) and CP (Nkrumah et al, 2006). When examining digestibility across RFI groups, the LRFI pigs had increased CAID digestibility of GE (P < 0.05; Table 2).…”
Section: Nutrient Digestibilitysupporting
confidence: 89%
“…This is in agreement with studies in cattle where RFI was correlated with improved dry matter digestibility (Richardson et al, 2004) and CP (Nkrumah et al, 2006). When examining digestibility across RFI groups, the LRFI pigs had increased CAID digestibility of GE (P < 0.05; Table 2).…”
Section: Nutrient Digestibilitysupporting
confidence: 89%
“…However, selection for RFI, has been reported to lead to reductions in methane emissions (Hegarty et al, 2007). Similar results were reported by Nkrumah et al (2006), in 27 steers they estimated a phenotypic correlation of 0.44 (P < 0.05) between RFI and methane production. In dairy cattle, de Haas et al (2011) suggested that by selecting for more efficient cows, methane production could be reduced by up to 26% over a 10-year time frame.…”
Section: Methanesupporting
confidence: 73%
“…These results demonstrated that in comparison with low genetic merit cows, high genetic merit cows had a lower enteric CH 4 emission per kg of DM intake and milk yield, and lower CH 4 -E outputs as a proportion of GE intake. Similar results have also been reported with beef cattle, namely that increasing production efficiency reduces daily enteric CH 4 (L/kg 0.75 ) production rate (Nkrumah et al, 2006) or CH 4 CH 4 = methane emission; PIN = profit index; PLI = profitable lifetime index; CH 4 -E = methane energy output; DM = dry matter; OM = organic matter; GE = gross energy; ME = metabolisable energy; ECMY = energy corrected milk yield. a,b,c Within a row, means without a common superscript letter differ significantly (P<0.05).…”
Section: Discussionsupporting
confidence: 80%